Formation of the Liaoshang gold deposit, Jiaodong Peninsula, eastern China: Evidence from geochronology and geochemistry. (13th January 2020) - Li, Junjian; Zhang, Pengpeng; Li, Guohua; Liu, Wengang; Zhao, Zhelin; Li, Xiuzhang; Ding, Zhengjiang; Fu, Chao; Tang, Wenlong; Dang, Zhicai; Tian, Jiepeng
Abstract : The Liaoshang gold deposit in the Jiaodong area of the Shandong Province is best known for its super‐large size. Situated on the north‐eastern margin of the Jiaolai Basin, it forms a part of the Jiaobei terrane of the North China Block. Approximately 20 ore bodies within the Liaoshang gold deposit have been explored; of these, four are structurally controlled gold‐bearing pyrite–dolomite vein‐type deposits. These ore bodies lie in an NE‐trending altered fracture zone and are characterized by their thickness and high‐grade ores. The wall rocks of the ore bodies consist of Paleoproterozoic Jingshan Group metamorphic rocks and Mesozoic granites. Gold is hosted mainly in pyrite and dolomite. The ore is divided into two subtypes—the dominant pyrite–dolomite vein subtype and the subordinate altered rock subtype which contains pyrite and dolomite. Fluid inclusions within dolomite indicate that the main metallogenic period was dominated by a CO2 –NaCl–H2 O fluid system that had low‐moderate salinity, low density, high abundance of CO2, and a small amount of N2 . The ore formed at 81‐ to 94‐MPa pressure and between 2.97‐ and 3.24‐km depth. Research on the S, Pb, C, O, and He–Ar isotopes in the gold‐bearing minerals suggests that the ore‐forming material was mainly crustal in origin, with some degree of crust–mantle mixing. The application of Rb–Sr isotope analysis to gold‐bearing pyrite yields a metallogenic age of 105.5 ± 9 Ma. The Sm–Nd isotope analysis of dolomite yields an age of 104.8 ± 5.1 Ma. We propose that gold mineralization in the Jiaodong area occurred in two phases: the early Early Cretaceous for gold deposits in the north‐west and the late Early Cretaceous for gold deposits in the east.